2018
DOI: 10.1002/lary.27393
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion in Head and Neck Cancer Patients Undergoing Pedicled Flap Reconstruction

Abstract: Objective Blood product utilization is monitored to prevent unnecessary transfusions. Head‐and‐neck pedicled flap reconstruction transfusion‐related outcomes were assessed. Methods One hundred and thirty‐six pedicled flap patients were reviewed: 64 supraclavicular artery island flaps (SCAIF), 57 pectoralis major (PM) flaps, and 15 submental (SM) flaps. Outcome parameters included flap‐related complications, medical complications, length of stay (LOS), and flap survival. Multivariable logistic regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…An animal experimentation study revealed that ANH could improve oxygenation in ischemic and hypoxic flap tissues [21]. Moreover, in a previous study, there were no differences in flap-related and medical complications between transfusion triggers of hematocrit less than 21% versus hematocrit less than 27% in free-flap reconstruction of the head and neck [22]. Thus, the present level of ANH for free-flap surgery was likely not to increase flap failure.…”
Section: Discussionmentioning
confidence: 83%
“…An animal experimentation study revealed that ANH could improve oxygenation in ischemic and hypoxic flap tissues [21]. Moreover, in a previous study, there were no differences in flap-related and medical complications between transfusion triggers of hematocrit less than 21% versus hematocrit less than 27% in free-flap reconstruction of the head and neck [22]. Thus, the present level of ANH for free-flap surgery was likely not to increase flap failure.…”
Section: Discussionmentioning
confidence: 83%
“…After leaving the OR, free flaps continue to place a greater burden on the healthcare system when compared with the SCF. An intriguing retrospective study by Abt et al 67 found that free flaps require more transfusions per patient than pedicled flaps. Free flaps routinely require postoperative ICU monitoring of the flap, typically in hourly increments.…”
Section: Resultsmentioning
confidence: 99%
“…2 The complication rate in SCF reconstructions has been reported at 25.5% (21%-31%). 66,67 Patients should be positioned postoperatively in a way that reduces pedicle tension. 51 There is also a risk of iatrogenic vascular injury causing flap necrosis, which is avoidable with careful dissection by an experienced surgeon.…”
Section: Complicationsmentioning
confidence: 99%
“…Patients will be considered for inclusion in the study if they meet all the following criteria: (1) age ≥18 years, (2) American Society of Anesthesiologists physical status I-IV, (3) scheduled oncologic surgical procedures with the intention to cure and (4) an overnight planned hospital admission. Patients who: (1) have planned ambulatory, revision or palliative surgery, (2) undergo surgeries with minimum risk of blood transfusion (≤1%) during and after (48 hours) surgery according to each centre practice, (3) emergency procedures or (4) scheduled surgery under local infiltration anaesthesia are not eligible in the study.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…However, not unfrequently, PRBCs are also given perioperatively to patients without haemodynamic instability or symptomatic anaemia. 2 As a result, the rate of PRBCs transfusions during and after major cancer surgery remains variable, but it can be as high as 90% and in some cases, such as thoracic surgeries, several units (>10) of blood products are given perioperatively. [3][4][5][6][7] Perioperative strategies of PRBCs transfusions may impact short-term clinical outcomes in patients with cancer.…”
Section: Introductionmentioning
confidence: 99%